Incorporating an Early Detection System Into Routine Clinical Practice in Two Community Hospitals. Issue 11 (2nd November 2016) - Dummett, B. Alex; Adams, Carmen; Scruth, Elizabeth; Liu, Vincent; Guo, Margaret; Escobar, Gabriel J.
Abstract : Efforts to improve outcomes of patients who deteriorate outside the intensive care unit have included the use of rapid response teams (RRTs) as well as manual and automated prognostic scores. Although automated early warning systems (EWSs) are starting to enter clinical practice, there are few reports describing implementation and the processes required to integrate early warning approaches into hospitalists' workflows. We describe the implementation process at 2 community hospitals that deployed an EWS. We employed the Institute for Healthcare Improvement's iterative Plan‐Do‐Study‐Act approach. Our basic workflow, which relies on having an RRT nurse and the EWS's 12‐hour outcome time frame, has been accepted by clinicians and has not been associated with patient complaints. Whereas our main objective was to develop a set of workflows for integrating the electronic medical record EWS into clinical practice, we also uncovered issues that must be addressed prior to disseminating this intervention to other hospitals. One problematic area is that of documentation following an alert. Other areas that must be addressed prior to disseminating the intervention include the need for educating clinicians on the rationale for deploying the EWS, careful consideration of interdepartment service agreements, clear definition of clinician responsibilities, pragmatic documentation standards, and how to communicate with patients. In addition to the deployment of the EWS to other hospitals, a future direction for our teams will be to characterize process‐outcomes relationships in the clinical response itself. Journal of Hospital Medicine 2016;11:S25–S31. © 2016 Society of Hospital Medicine